Does Village Funds Impact on Reducing Poverty and Improving Good Governance Practices? - Anshori, Saiful Muhammad; Bukhori, Achmad Aditama (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2018)
Village fund programs have been implemented fairly well, except in the case of good governance practices need to be continuously strengthened. Teruta is related to the understanding of the village apparatus, especially BPD, against administrative guidelines for program implementation. Moreover, in reality, the village funding program is very much against the good governance practices and the spirit of poverty reduction. So the benefits received from village funding programs for the poor are very small compared to richer communities. Almost in all study villages, there is a decrease in poverty but the role of village funds in the reduction of poverty is not seen significantly by the citizens. Village funding programs are considered more indirect in reducing poverty, by improving public infrastructure to facilitate public access to public facilities. The creation of employment in village fund infrastructure projects is also not enough to help the poor. In addition to the very limited number of days and unnecessary workers from among the poor.